2000
DOI: 10.1016/s0198-9715(00)00017-x
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the pattern of urban growth with PUP: a web-based model interfaced with GIS and 3D animation

Abstract: ABSTRACT. This paper describes a model (PUP -Projections for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Urban infill, a basic process in urbanization and a threat to greenbelts, has been captured in a number of modeling studies (Bell at al., 2000;Wilson et al, 2003;Syphard et al, 2005). Many modeling studies with SLEUTH use historical growth patterns for calibration and then use four specific growth types-random dispersion, expansion from spontaneous urbanization (sprawl), expansion from settlements, and growth along transportation networks (e.g., Jantz et al, 2003;Syphard et al, 2005;Oguz et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Urban infill, a basic process in urbanization and a threat to greenbelts, has been captured in a number of modeling studies (Bell at al., 2000;Wilson et al, 2003;Syphard et al, 2005). Many modeling studies with SLEUTH use historical growth patterns for calibration and then use four specific growth types-random dispersion, expansion from spontaneous urbanization (sprawl), expansion from settlements, and growth along transportation networks (e.g., Jantz et al, 2003;Syphard et al, 2005;Oguz et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This book is a sequel to the book, "Global Environmental Databases" which was published in July 2000 as one of the activities by the International Society for Photogrammetry and Remote Sensing (ISPRS Working Group IV/6 (1996-2000. The following Working Group IV/8 (2000-2004 on "Global Environmental Databases" has taken over this activity by the same cochairmen, Tateishi and Hastings.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a growing trend Municipalities' limits in the study area towards the combined use of geographical information systems and spatial remote sensing (Hinton 1996, Poulter 1995, Brown and Fletcher 1994, Dobson 1993, Staret et al 1991, Nellis et al 1990). Those tools can provide a general view of all the urban and suburban components (Haala andBrenner 1999, Anys et al 1998a) and offer spatio-temporal follow-up that can be readily adapted to observed phenomena (Bell et al 2000, Batty et al 1999, Trotter 1991, Meaille and Wald 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Chi & Voss, 2011), land-use/ housing-unit (e.g. Bell et al, 2000), exponential smoothing (e.g. Walters & Cai, 2008), all-age component (e.g.…”
Section: Individual Modelsmentioning
confidence: 99%